A typology of organizational readiness for change based on a latent profile analysis - Köhler, Alina; Ritter, Marie; Kauffeld, Simone (Frontiers in Psychology, 2024)
Companies have to undergo many change processes to succeed in the transforming economy. However, many change processes fail because employees are insufficiently accompanied through the process in a targeted manner. This study of N = 427 employees from a steel industry company undergoing a transformation process examines whether the organizational readiness for change (ORC) of highly affected employees can be classified into profiles, how these profiles can be predicted by various antecedents, and whether outcome variables such as job satisfaction can be explained by profile membership. Based on five facets of ORC (i.e., individual valence and positive affect), a total of six ORC profiles were identified: Proactives, Acceptors, Opens, Neutrals, Reluctants and Deniers. Employees’ optimism and the degree of perceived interpersonal and informational fairness can predict profile membership. It was shown that profiles significantly differ in relevant outcome variables satisfaction and intention to leave. These results contribute to the basic understanding of ORC and provide an initial approach for improving ORC profiles which could increase the success rate of change processes in companies.